Formulación del plan estratégico como instrumento de gestión para mejorar la competitividad de la empresa Turismo Moche Trujillo, período 2017 - 2020 - Julián Mantilla, Elizabeth Jocelyn (2017)
This research study aims to formulate a strategic plan as a management tool based on the integral scorecard for the Turismo Moche company, which will allow the identification of existing organizational failures, improve them and formulate strategies that will enable this entity to lead the market in which it is developed. The problem is formulated: To what extent does the formulation of a strategic plan as a management tool improve the competitiveness of the Turismo Moche company from 2017 - 2020? considering as hypothesis that the formulation of a strategic plan as a management tool improves competitiveness of the company Tourism Moche period 2017 - 2020. For the present research report descriptive design was used, as well as the methods: inductive, deductive, analytical and hypothetic-deductive. A field work (interview) and surveys will be carried out; as well as information provided by the owner of the company. During the internal and external study of the company, the following results were found: the disorganization of the company due to the lack of an administrative structure, the lack of objectives and strategies to face the constant challenges of the market in which it is developed, the company does not have an orientation for the development of marketing and the use of social networks, it does not have the necessary technology to improve the service offered by the company, it was determined that when implementing the proposal of the strategic plan, the company will obtain an integrated management system with an appropriate organizational design which will help to improve the competitiveness of the Turismo Moche company. In the present investigation it was concluded that a strategic plan will allow the Turismo Moche company to be more competitive in the market. The strategic plan allows controlling the strategies and competitive advantages, comparing them with other rival companies by analyzing in this way to know if it is necessary to improve or redesign the existing strategies. The follow-up to the fulfillment of the objectives must be constant on the part of the responsible of management, and of each person that contributes to these objectives; the company has to be fully committed.